Sie bewegten die Welt Lebensbilder unserer Zeit - Quadflieg, Josef 1924-2020 (Patmos, 2000)
Henry Dunant. Bertha von Suttner. Elsa Brandström. Fridtjof Nansen. Marie Curie. Maria Montessori. Albert Einstein. Albert Schweitzer. Marie Juchacz. Käthe Kollwitz. Dietrich Bonhoeffer. Hans Scholl. Janusz Korczak. Maximilian Kolbe. Johannes XXIII. Mutter Teresa. Willy Brandt. Mahatma Gandhi. Martin Luther King. Nelson Mandela.